∆Np63/p40 correlates with the location and phenotype of basal/mesenchymal cancer stem‐like cells in human ER+ and HER2+ breast cancers - Yajing Liu; Marta Nekulova; Rudolf Nenutil; Iva Horakova; M Virginia Appleyard; Karen Murray; Jitka Holcakova; Michaela Galoczova; Philip Quinlan; Lee B Jordan; Colin A Purdie; Borivoj Vojtesek; et al. (Wiley, 2020)
Abstract ΔNp63, also known as p40, regulates stemness of normal mammary gland epithelium and provides stem cell characteristics in basal and HER2‐driven murine breast cancer models. Whilst ΔNp63/p40 is a characteristic feature of normal basal cells and basal‐type triple‐negative breast cancer, some receptor‐positive breast cancers express ΔNp63/p40 and its overexpression imparts cancer stem cell‐like properties in ER+ cell lines. However, the incidence of ER+ and HER2+ tumours that express ΔNp63/p40 is unclear and the phenotype of ΔNp63/p40+ cells in these tumours remains uncertain. Using immunohistochemistry with p63 isoform‐specific antibodies, we identified a ΔNp63/p40+ tumour cell subpopulation in 100 of 173 (58%) non‐triple negative breast cancers and the presence of this population associated with improved survival in patients with ER−/HER2+ tumours (p = 0.006). Furthermore, 41% of ER+/PR+ and/or HER2+ locally metastatic breast cancers expressed ΔNp63/p40, and these cells commonly accounted for <1% of the metastatic tumour cell population that localised to the tumour/stroma interface, exhibited an undifferentiated phenotype and were CD44+/ALDH−. In vitro studies revealed that MCF7 and T47D (ER+) and BT‐474 (HER2+) breast cancer cell lines similarly contained a small subpopulation of ΔNp63/p40+ cells that increased in mammospheres. In vivo, MCF7 xenografts contained ΔNp63/p40+ cells with a similar phenotype to primary ER+ cancers. Consistent with tumour samples, these cells also showed a distinct location at the tumour/stroma interface, suggesting a role for paracrine factors in the induction or maintenance of ΔNp63/p40. Thus, ΔNp63/p40 is commonly present in a small population of tumour cells with a distinct phenotype and location in ER+ and/or HER2+ human breast cancers.